(untitled) (Indian Journal of Arid Horticulture, 2025)
Kachari (Cucumis callosus) is an important cucurbitaceous vegetable grown in arid region of Western Rajasthan. The quality attributes with reference to microbial contamination, their role on nutrients depletion and myco toxicity are important concern in any post harvest products prepared from fruits and vegetables. Different products are prepared from vegetables and stored for long and short term but storage of post harvest products after convenient treatment is important to maintain the nutritional status and hygienic level under various conditions. Out of different horticultural crops of arid region, very limited works on post harvest process and storage conditions have been carried in crops like pomegranate. Low temperature (2°C) was suitable for fruits with flavour similar to that at harvest but main losses occurred by Penicillium spp. at 5°C and the quality and shelf-life of pomegranate could be improved by curing at 2°C and intermittent warming during cold storage (Artes et al., 1996; 2000). However, post harvest pathogens can spoil those products stored under unhygienic conditions having favourable climatic conditions for growth and sporulation. Kanwar et al.